The Impact of Statement of Financial Accounting Standards No. 8 on the Foreign Exchange Risk Management Practices of American Multinationals: An Economic Impact Study (Book). - Shank, John K. (The Accounting Review, 1979)
Reviews the book "The Impact of Statement of Financial Accounting Standards No. 8 on the Foreign Exchange Risk Management Practices of American Multinationals: An Economic Impact Study," by Thomas G. Evans, William R. Folks and Michael Jilling.